Study of muon-pair production at centre-of-mass energies from 20 to 136 GeV with the ALEPH detector - BARATE, R. (Institutional Knowledge at Singapore Management University, 1997)
The total cross section and the forward-backward asymmetry for the process e+e− → μ+μ−(nγ) are measured in the energy range 20–136 GeV by reconstructing the effective centre-of-mass energy after initial state radiation. The analysis is based on the data recorded with the ALEPH detector at LEP between 1990 and 1995, corresponding to a total integrated luminosity of 143.5 pb−1. Two different approaches are used: in the first one an exclusive selection of events with hard initial state radiation in the energy range 20–88 GeV is directly compared with the Standard Model predictions showing good agreement. In the second one, all events are used to obtain a precise measurement of the energy dependence of σ0 and AFB0 from a model independent fit, enabling constraints to be placed on models with extra Z bosons.